CLASS AND SOCIAL INEQUALITY IN IAN MCEWAN’S ATONEMENT (Journal of Contemporary Philology, 2020)
Atonement, perhaps Ian McEwan’s best-known novel, is considered an epic of British postmodernist literature because it touches on a variety of contemporary topics. Although Atonement focuses primarily on themes such as love and repentance, it also deals with social class, status, and power, which are analysed in this paper. Furthermore, social stratification and inequality form the crux of this analysis. Using Max Weber’s theory of social stratification, and the characters as examples, this research considers how much social division truly exists in the novel, which serves as a mirror to British society. Moreover, various forms of social mobility are examined, as well as the solutions to those problems which are not only present in fiction, but also in reality. Ian McEwan’s Atonement talks about these issues and more, he sets problems and poses questions that challenge our lives’ perspectives, hence making it a unique literary gem.
Keywords: social class; stratification; inequality; atonement; sociology